2018
DOI: 10.18671/scifor.v46n118.17
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho técnico, econômico e ambiental do harvester em distintas rotações do motor

Abstract: A presente pesquisa teve como objetivo analisar o desempenho técnico, econômico e as emissões de gases causadores de efeito estufa emitidos pelo harvester operando em diferentes rotações do motor. A pesquisa foi executada em áreas de colheita florestal, localizadas na região sul do estado da Bahia. Foi realizado um estudo de tempos e movimentos; produtividade; consumo horário de combustível; emissão de dióxido de carbono, metano e óxido nitroso; custo operacional e de produção, sendo todos os parâmetros analis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…Regarding the engine speed, the machine behavior for hourly fuel consumption was similar to the results found by Santos et al (2018), Ramos et al (2016), and Fiorese et al (2015). Despite the technical differences between the machines, it is clear that operators work at maximum engine speeds regardless of operating conditions and without regard to high hourly fuel consumption.…”
Section: Technical Parameterssupporting
confidence: 83%
See 1 more Smart Citation
“…Regarding the engine speed, the machine behavior for hourly fuel consumption was similar to the results found by Santos et al (2018), Ramos et al (2016), and Fiorese et al (2015). Despite the technical differences between the machines, it is clear that operators work at maximum engine speeds regardless of operating conditions and without regard to high hourly fuel consumption.…”
Section: Technical Parameterssupporting
confidence: 83%
“…The operator reported that he was psychologically affected by the fact that engine speed and hydraulic pump flow could be reduced. Santos et al (2018) evaluated a Volvo brand excavator-based harvester operating at different engine speeds in a 0.25 m 3 tree -1 forest stand and concluded that the engine speed regime does not cause significant changes in operational performance. In the research conducted by Ramos et al (2016), it was found that the engine speed regime in the range of 1800 to 2100 rpm does not affect the operating performance of a sugarcane harvester when operating at speeds up to 4 km h -1 ; however, productivity is significantly influenced at higher speeds.…”
Section: Technical Parametersmentioning
confidence: 99%
“…Despite the advantages of the forwarder operation, it has a high operating cost, and fuel is the fourth greatest expense, representing about 14% of the total cost (Santos et al, 2016;Robert et al, 2018). Reducing engine speed and hydraulic pump pressure is an alternative that has been used to reduce the hourly fuel consumption of machines and consequently the overall cost (Prinz et al, 2018;Santos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Prinz et al (2018) the harvester's work settings affect fuel consumption, with the best results being obtained in the operating modes that have the lowest engine speed regime. According to Santos et al (2018) reducing harvester engine speed causes significant decreases in hourly fuel consumption. In the research developed by Spinelli et al (2018) it was found that simply adjusting the engine rpm reduces fuel consumption and does not affect the productivity of wood chippers.…”
Section: Introductionmentioning
confidence: 99%